Indonesia-Singapore Cooperation in Ratification of Extradition Treaty for Corruption Fugitives - Ridho, Dandy; Sagena, Uni (Research Horizon, 2023)
The extradition treaty between Indonesia and Singapore plays a vital role in fostering bilateral cooperation in combating transnational crimes and ensuring the effective administration of justice in both nations. This study aims to assess and analyze the treaty’s key provisions, legal frameworks, mechanisms, and implications for extradition arrangements between these neighboring Southeast Asian countries. By examining the historical context and evolution of the treaty, this research sheds light on the challenges, successes, and potential areas for improvement in the extradition process. Drawing on comparative legal analysis and case studies, this study contributes to understanding the impact of the treaty on extradition practices, bilateral relations, and how it aligns with international standards. In doing so, it highlights the importance of efficient extradition mechanisms in addressing contemporary criminal challenges, promoting regional security cooperation, and upholding human rights values within the context of Indonesia and Singapore.